2003
DOI: 10.3748/wjg.v9.i12.2666
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial infusion chemotherapy for hepatocellular carcinoma with tumor thrombosis of the portal vein

Abstract: AIM: Hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) is associated with poor prognosis. The aim of this prospective study was to evaluate the efficacy of hepatic arterial infusion chemotherapy (HAIC) for patients with this disease. METHODS:Eighteen HCC patients with PVTT were treated with HAIC via a subcutaneously implanted injection port. A course of chemotherapy consisted of daily cisplatin (10 mg for one hour) followed by 5-fluorouracil (250 mg for five hours) for five continuous day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 43 publications
4
42
1
Order By: Relevance
“…With regard to the adverse reactions to intra-arterial low-dose cisplatin and 5-FU, nausea, loss of appetite, peptic ulcer, leukopenia, thrombocytopenia, deterioration of hepatic function, and renal damage have been reported in previous studies [11][12][13] . Most of these adverse reactions were considered to be relatively mild and no patient required administration of G-CSF or blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the adverse reactions to intra-arterial low-dose cisplatin and 5-FU, nausea, loss of appetite, peptic ulcer, leukopenia, thrombocytopenia, deterioration of hepatic function, and renal damage have been reported in previous studies [11][12][13] . Most of these adverse reactions were considered to be relatively mild and no patient required administration of G-CSF or blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of HCC patients with PVTT in the trunk is reported to be about 90 d with supportive care [28] . Three recent studies have reported the efficacy and survival benefits of combination therapy of intra-arterial low-dose cisplatin and 5-FU for patients with advanced HCC [11][12][13] . These studies included nine, 48 and 18 patients with advanced HCC and PVTT (in the second branch, first branch, or trunk), who showed objective response rates of 44% (4/9 patients), 48% (23/48 patients) and 33% (6/18 patients), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, the response rate and disease control rate of HAIC in advanced HCC patients with PVTT [11,[24][25][26] were 33%-52% and 47%-77%, respectively. The median OS was 7-10 mo in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Any subjects whose hepatic tumors are diagnosed as other than HCC or who have extrahepatic metastases at the entry were excluded from this study. The modalities of treatment include transcatheter arterial embolization (TAE) [14,[17][18][19], transcatheter arterial infusion (TAI) chemotherapy [20][21][22][23][24], percutaneus ethanol injection (PEI) [25], percutaneus microwave coagulation therapy (PMCT) [11], radiofrequency ablation (RFA) [26][27][28], radiation therapy (RT) [29][30][31][32], and hepatic resection [5]. No antiviral drugs were given as an adjuvant therapy to any patient in this study.…”
Section: Study Populationmentioning
confidence: 99%